1999
DOI: 10.1161/01.cir.100.10.1116
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cardiotrophin-1 in Cardiac Myocyte-Nonmyocyte Interactions During Hypertrophy of Rat Cardiac Myocytes In Vitro

Abstract: These results show that CT-1 secreted from cardiac nonmyocytes is significantly involved in the hypertrophic changes of cardiac myocytes in the coculture and suggest that CT-1 is an important local regulator in the process of cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 24 publications
4
71
0
1
Order By: Relevance
“…Interactions occur between cardiomyocytes and fibroblasts in the heart 4,22) . In this study, we demonstrated that the cardiac fibroblast -conditioned medium (CM) ameliorates the survival of cardiomyocytes in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactions occur between cardiomyocytes and fibroblasts in the heart 4,22) . In this study, we demonstrated that the cardiac fibroblast -conditioned medium (CM) ameliorates the survival of cardiomyocytes in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…), and the beating hearts were then excised. The aorta was quickly connected to the Langendorff's apparatus, suspended, and perfused with Krebs -Henseleit buffer (NaCl 118 mmol/L, KCl 4.7 mmol/L, MgSO 4 1.2 mmol/L, KH 2 PO 4 1.2 mmol/L, CaCl 2 1.8 mmol/L, NaHCO 3 25 mmol/L, glucose 11 mmol/L, pH 7.4), oxygenized with 95% O 2 and 5% CO 2 , and warmed at a constant temperature of 37°C 17) . The left atrium was opened and a latex balloon was inserted into the left ven-tricle (LV) to determine the left ventricular end -diastolic pressure (LVEDP).…”
Section: Langendorff's Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, we here investigated whether CF co-cultured with CM changed the development of the functional characteristics of cardiac myocytes. In fact, previous studies have revealed that non-myocytes secrete a humoral factor such as endothelin-1 (ET-1) or cardiotrophin-1 (CT-1) regulating the development of cardiac myocytes (Harada et al, 1997;Kuwahara et al, 1999). However, there is a possibility that MC-MC interactions are also critical to the development of MC themselves.…”
Section: Myocyte-enriched Cultures (Cm) Co-cultures Of Cardiac Myocymentioning
confidence: 99%
“…In fact, previous studies have revealed that non-myocytes secrete a humoral factor such as endothelin-1 (ET-1) or cardiotrophin-1 (CT-1) regulating the development of cardiac myocytes (Harada et al, 1997;Kuwahara et al, 1999).…”
Section: Introductionmentioning
confidence: 99%